Predictive and prognostic roles of BRAF mutation in patients with metastatic colorectal cancer treated with anti‐epidermal growth factor receptor monoclonal antibodies: A meta‐analysis. Issue 8 (4th July 2013) - Xu, Qi; Xu, An Tao; Zhu, Ming Ming; Tong, Jin Lu; Xu, Xi Tao; Ran, Zhi Hua
<x xml:space="preserve">Abstract</x> Objective This study aimed to evaluate the predictive and prognostic roles of BRAF mutation in patients with metastatic colorectal cancer (mCRC) treated with anti‐epidermal growth factor receptor (EGFR) monoclonal antibodies (MoAbs). Methods Computer searches of the literature on BRAF mutation in mCRC patients were performed. Studies with objective response rate (ORR) to anti‐EGFR MoAbs and/or overall survival (OS) and progression‐free survival (PFS) with different BRAF gene expression in mCRC patients were eligible. Results A total of 19 studies including 2875 patients was enrolled in the meta‐analysis. BRAF mutation was detected in 246 patients. The ORR was 18.4% (40/217) in mutant BRAF group and 41.7% (831/1993) in the wild‐type BRAF group. The overall risk ratio (RR) for the ORR of BRAF mutation patients compared with wild‐type BRAF patients was 0.58 (95% confidence intervals [CI] 0.35–0.94, P = 0.027). The median PFS of patients with BRAF mutation was significantly shorter than that of patients with wild‐type BRAF (hazard ratio [HR] 2.98, 95% CI 2.07–4.27, P < 0.001) and the median OS of patients with BRAF mutation was also significantly shorter than that of those with wild‐type BRAF (HR 2.85, 95% CI 2.31–3.52, P < 0.001). Conclusion BRAF mutation is associated with poor response to anti‐EGFR MoAbs and it is an adverse prognostic biomarker of the survival of patients with mCRC.